METODE CONTEXTUAL TEACHING AND LEARNING UNTUK PENGEMBANGAN PEMBELAJARAN PAI - Akbar, Rofiq Faudy (EDUKASIA, 2012)
There are many limitations in the ï¬ gure of a teacher, the limitations in the mastery of knowledge, limitations in management/class management,and limitations in understanding the character of each learner. Teachers mustreconstruct the learning design has been applied, especially in style or methodof teaching. Selection of an appropriate method will be able to overcome theselimitations and give effect on the learning process that will take place. One of learning method to create effective learning, creating an atmosphereof fun and not boring (joyfull and quantum learning), providing real-worldexperience (real world learning) and using a variety of learning resources is themethod of Contextual Teaching and Learning (CTL) or Learning in Context.Contextual Teaching and Learning methods are very suitable to be appliedin the teaching of Islamic Education because it is focused on understanding,development of knowledge, skills and contextual understanding of the studentsabout the subjects relationship to what students encountered in daily life. Key words: Contextual Teaching and Learning, learning method,IslamicReligious Education